2018
DOI: 10.2334/josnusd.17-0109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface treatments on repair bond strength of a new CAD/CAM ZLS glass ceramic and two different types of CAD/CAM ceramics

Abstract: We evaluated the effects of three different surface treatments and two different bonding procedures on shear bond strength of resin composites to different computer-aided design/manufacturing (CAD/CAM) ceramics with or without thermocycling. The test specimens were prepared from three different CAD/CAM ceramics (Group A, IPS e.max CAD; Group B, IPS e.max ZirCAD; Group C, Vita Suprinity). They were divided into eight subgroups according to the surface treatment and bonding procedures. After resin composite was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…The second hypothesis that HF acid etching time affects the substrate’s surface morphology and SBS was confirmed. The highest SBS values for all tested CAD/CAM ceramic materials were observed after etching times of 15 s to 60s, which were accompanied by increased structural irregularities and undercuts due to removal of ceramic particles that are responsible for sufficient micromechanical retention [36, 63]. In the present study differing etching patterns were observed for EC between 15 s and 30s that did not affect SBS values.…”
Section: Discussionmentioning
confidence: 59%
“…The second hypothesis that HF acid etching time affects the substrate’s surface morphology and SBS was confirmed. The highest SBS values for all tested CAD/CAM ceramic materials were observed after etching times of 15 s to 60s, which were accompanied by increased structural irregularities and undercuts due to removal of ceramic particles that are responsible for sufficient micromechanical retention [36, 63]. In the present study differing etching patterns were observed for EC between 15 s and 30s that did not affect SBS values.…”
Section: Discussionmentioning
confidence: 59%
“…20 Er,Cr:YSGG laser with a wavelength of 2.78 µm has been used for surface roughening of different CAD/ CAM materials in the literature. [21][22][23] According to Kirmali et al, 24 when roughening the composite surfaces with 1.5-W, 2-W, and 3-W Er,Cr:YSGG laser irradiation, rough and irregular surfaces occur and acceptable shear bond strength similar to sandblasting is obtained. Barutcigil et al 23 also reported a mean SBS of 9.137 MPa for Er,Cr:YSGG laserirradiated Vita Enamic specimens at 2 W. According to the same study, this result was found to be similar to those obtained from CoJet sandblasting, 50-µm Al 2 O 3 sandblasting, and 10% HF acid etching surface treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] These findings were comparable with the repair bond values in group 4 (AA-S) and also validate the findings in the study by Colares et al 15 and Ataol and Ergun. 27 The highest repair bond strength in case of HRC was observed in AA-S (20.52 ± 2.51 MPa), followed by HFA-S Table 2). A probable description to these conclusions is that aluminium trioxide particle (Al 2 O 3 ) abrades and roughens the ceramic surface under defined pressure.…”
Section: Discussionmentioning
confidence: 88%